Analisis Pengurangan Produk Cacat pada Produksi Kerupuk Bawang dengan Metode Six Sigma pada UD. Rukun Jaya Pasuruan - Aryaseta, Aziz Wisnu; Ardiansyah, Rafli Dwi; Imanuddin, Rahmat; Putra, Muhammad Hengki Riawan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Failed products are a challenge for business people in doing business. UD. Rukun Jaya produces food products, namely onion crackers. The problem encountered in this business is product defects resulting from the onion cracker production process which causes the average percentage of defective products for the period January - April 2024 to be 4.22% with a sigma value of 4.59. The type of defect that dominates is onion crackers, namely crushed onion crackers, unsold products, hard texture, and damaged packaging. This failure is actually trivial, but it can disappoint customers. This research aims to provide a solution in the hope of reducing the number of product defects produced using the six sigma and FMEA methods. This research produces information on the causes of defective product problems, dominated by the type of defect in broken or crushed crackers and unsold crackers. The type of defect in crushed keupuk products is dominated by suppliers and employees who are not careful when frying and shipping. Meanwhile, the product did not sell because the employees were not good at marketing and what was more, there was no good marketing strategy and the crackers sold were not diverse enough.